PRRSV-2 viral load in critical non-lymphoid tissues is associated with late gestation fetal compromise - Rudy, K.; Jeon, D.; Smith, A. A.; Harding, J. C. S.; Pasternak, J. A. (Frontiers in Microbiology, 2024)
The impact of late gestation PRRSV-2 infection is highly variable within a litter, with a subset of fetuses displaying varying degrees of compromise following infection while others remain viable despite significant systemic viral load. To understand the underlying cause of this variation, we examined the susceptibility, distribution and impact of viral infection within non-lymphoid tissues. Samples of brain, heart, kidney, liver, lung, and skeletal muscle were obtained from fetuses of pregnant gilts at gestation day 86, and the presence and distribution of CD163+ cells within each tissue evaluated via immunohistofluorescence. Equivalent samples were collected from phenotypic extremes representing resistant, resilient and susceptible fetuses at 21 days following infection of pregnant gilts with PRRSV-2 at day 86 of gestation. Viral load and its impact in each tissue was evaluated by a combination of qPCR, in vitro viral recovery, and local expression of IFNG and CD163. Resting populations of CD163+ cells were observed in all six non-lymphoid tissues from healthy day 86 fetuses, though the apparent density and the morphology of positive cells varied between tissue. Viral RNA was detected in all six tissues derived from fetuses previously classified as highly infected, and infectious viral particles successfully recovered. Significantly more viral RNA was detected in heart, brain, lung and skeletal muscle of susceptible fetuses, relative to their viable counterparts. Infection was associated with an increase in the expression of CD163 in brain, kidney and lung. In addition, the presence of virus in each tissue coincided with a significant upregulation in the expression of IFNG, but the scale of this response was not associated with fetal susceptibility. Thus, PRRSV-2 is widely distributed across these susceptible non-lymphoid fetal tissues, and fetal outcome is associated with local viral load in critical fetal organs.